Preparation of bi-layer composite films for controlled cefazolin delivery and enhanced antibacterial activity - Sanliturk, Gizem; Guran, Mumtaz; Gazi, Mustafa (Taylor & Francis Ltd, 2025)
In the present study, a wide-spectrum antibiotic drug, cefazolin was loaded into novel bi-layer composite films based on chitosan and alginate. The objective was to achieve sustained antibacterial activity at the application site, while enhancing the local efficacy of cefazolin. The physical properties of the composite films were characterized using techniques including FTIR, XRD, and SEM. Additionally, drug content uniformity, contact angle, weight variation, swelling index, drug release profiles, and kinetics were investigated. Antibacterial efficacy of the films was evaluated against Methicillin-resistant Staphylococcus aureus (MRSA), an important drug resistant pathogen. Multiple assays including time-kill, disk diffusion, and microbial penetration assays were employed to comprehensively assess various parameters of antibacterial action. The results demonstrated homogenous drug distribution and minimal weight variation in the films. Well-compatible film formations were shown by the SEM micrographs. Cefazolin release was sustained for 1440 min, and the release kinetics were fitted with the Korsmeyer-Peppas model. The fabricated films exhibited significant and sustained antibacterial activity against MRSA for a duration of 900 minutes, ultimately leading to complete eradication of viable bacterial populations. Taken together, novel films demonstrated good mechanical properties and hold great promise for biomedical applications, offering extended antibiotic release and sustained pathogen eradication.
Keywords: Alginate; antibacterial; cefazolin; chitosan; composite film; drug-delivery; MRSA